Genome sequencing unveils mutational landscape of the familial Mediterranean fever: Potential implications of IL33/ST2 signalling - Meenakshi Umar (492911) (2020)
Familial Mediterranean fever (FMF) is the most common auto-inflammatory disease. It is transmitted as autosomal recessive trait with mutations in MEditerranean FeVer (MEFV) gene. Despite a typical clinical expression, many patients have either a single or no mutation in MEFV. The current work is aimed to revisit the genetic landscape of FMF disease using high-coverage whole genome sequencing. In atypical patients (carrying a single or no mutation in MEFV), we revealed many rare variants in genes associated with auto-inflammatory disorders, and more interestingly, we discovered a novel variant ( a 2.1-Kb deletion) in exon 11 of IL1RL1 gene, present only in patients. To validate and screen this patient-specific variant, a tandem of allele-specific PCR and quantitative real-time PCR was performed in 184 FMF patients and 218 healthy controls and we demonstrated that the novel deletion was absent in controls and was present in more than 19% of patients. This study sheds more light on the mutational landscape of FMF. Our discovery of a disease-specific variant in IL1RL1 gene may constitute a novel genetic marker for FMF. This finding suggesting a potential role of the IL33/ST2 signalling in the disease pathogenicity highlights a new paradigm in FMF pathophysiology. Other Information Published in: Journal of Cellular and Molecular Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1111/jcmm.15701